Erbium luminescence in the TiO2 and SrTiO3 thin films - M. V. Rudenko; L. S. Khoroshko; N. V. Gaponenko; A. V. Mudryi; T. F. Raichyonok (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Erbium doped titania and strontium titanate thin films were synthesized by the sol-gel method on the quartz glass, monocrystalline silicon and porous anodic alumina/silicon structures. Morphology of the surface and optical properties of the films were investigated. Luminescence spectra of the thin films show an intense band at 1.53 µm corresponding to the electronic transitions (4I13/2→4I15/2) of the erbium trivalent ions.